In vitro degradation of PHBV scaffolds and nHA/PHBV composite scaffolds containing hydroxyapatite nanoparticles for bone tissue engineering - Sultana, Naznin (Hindawi Publishing Corporation, 2012)
This paper investigated the long-term in vitro degradation properties of scaffolds based on biodegradable polymers and osteoconductive bioceramic/polymer composite materials for the application of bone tissue engineering. The three-dimensional porous scaffolds were fabricated using emulsion-freezing/ freeze-drying technique using poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) which is a natural biodegradable and biocompatible polymer. Nanosized hydroxyapatite (nHA) particles were successfully incorporated into the PHBV scaffolds to render the scaffolds osteoconductive. The PHBV and nHA/PHBV scaffolds were systematically evaluated using various techniques in terms of mechanical strength, porosity, porous morphology, and in vitro degradation. PHBV and nHA/PHBV scaffolds degraded over time in phosphate-buffered saline at 37()C. PHBV polymer scaffolds exhibited slow molecular weight loss and weight loss in the in vitro physiological environment. Accelerated weight loss was observed in nHA incorporated PHBV composite scaffolds. An increasing trend of crystallinity was observed during the initial period of degradation time. The compressive properties decreased more than 40% after 5-month in vitro degradation. Together with interconnected pores, high porosity, suitable mechanical properties, and slow degradation profile obtained from long-term degradation studies, the PHBV scaffolds and osteoconductive nHA/PHBV composite scaffolds showed promises for bone tissue engineering application.